Process optimization for large-scale hydrogen liquefaction. (27th April 2017) - Cardella, U.; Decker, L.; Sundberg, J.; Klein, H.
Abstract: The investment in the hydrogen infrastructure for hydrogen mobility has lately seen a significant acceleration. The demand for energy and cost efficient hydrogen liquefaction processes has also increased steadily. A significant scale-up in liquid hydrogen (LH2 ) production capacity from today's typical 5–10 metric tons per day (tpd) LH2 is predicted for the next decade. For hydrogen liquefaction, the future target for the specific energy consumption is set to 6 kWh per kg LH2 and requires a reduction of up to 40% compared to conventional 5 tpd LH2 liquefiers. Efficiency improvements, however, are limited by the required plant capital costs, technological risks and process complexity. The aim of this paper is the reduction of the specific costs for hydrogen liquefaction, including plant capital and operating expenses, through process optimization. The paper outlines a novel approach to process development for large-scale hydrogen liquefaction. The presented liquefier simulation and cost estimation model is coupled to a process optimizer with specific energy consumption and specific liquefaction costs as objective functions. A design optimization is undertaken for newly developed hydrogen liquefaction concepts, for plant capacities between 25 tpd and 100 tpd LH2 with different precooling configurations and a sensitivity in the electricity costs. Compared to a 5 tpd LH2 plant, the optimized specific liquefaction costs for a 25 tpd LH2 liquefier are reduced by about 50%. The high-pressure hydrogen cycle with a mixed-refrigerant precooling cycle is selected as preferred liquefaction process for a cost-optimized 100 tpd LH2 plant design. A specific energy consumption below 6 kWh per kg LH2 can be achieved while reducing the specific liquefaction costs by 67% compared to 5 tpd LH2 plants. The cost targets for hydrogen refuelling and mobility can be reached with a liquid hydrogen distribution and the herewith presented cost-optimized large-scale liquefaction plant concepts. Highlights: Simulation and optimization of newly developed hydrogen liquefaction processes. Specific liquefaction costs and energy consumption as optimization objectives. HP-H2 cycle with MRC precooling as preferred liquefaction process up to 100 tpd. Specific liquefaction costs: reduced by about 50% at 25 tpd and by 67% at 100 tpd. Energy consumptions ≤6 kWh per kg LH2 feasible with low technical risk.